Comparison Study Between Fine Needle Aspiration Cytology and Tru-Cut Biopsy in Diagnosis of Suspected Carcinoma of Palpable Breast Mass in Female Patients - Kadhom, Dr. Abere Basim; Sarsam, Dr. Saad Abdulla (Academic Journal of Clinicians, 2024)
Background: The diagnosis of tumors in the breast is commonly conducted by the triple assessment including a surgeon, radiologist, and pathologist. Both fine-needle aspiration cytology (FNAC) and Trucut biopsy (TCB) are utilized procedures, each with its distinct advantages and limitations. Objective: To show sensitivity & specificity of Trucut biopsy in diagnosis of CA breast & compared it with FNAC. Patients and Methods: This prospective study included a total of 80 female patients with breast lump. 80 patients who attended the outpatient clinic at Baghdad Medical city complex during period from January 2020 to July 2021, have been underwent FNAC and TCB, while all included patients had ultrasound and / or mammography and histopathology. The diagnostic value of FNAC and TCB was compared with final histopathology result. Results: the sensitivity and specificity of TCB was 96.97% and 92.85% respectively. The positive and negative predictive value of this assay are 98.46% and 86.67%, respectively. The sensitivity and specificity of FNAC will be 83.33% and 85.71% respectively. The positive and negative predictive value of this assay are 96.49% and 52.17%, respectively. The agreement between TCB and histopathology was found to be excellent (κ= 0.893, 95%CI= 0.748-0.949, p<0.001). On the other hand, there was a moderate agreement between FNA and histopathology (κ= 0.620, 95%CI= 0.592-0.638, p<0.001). Conclusions: Trucut biopsy is moreinformativethan FNAC in diagnosis of suspected cases of breast cancer. The agreement between TCB and histopathology was excellent (κ= 0.893, 95%CI= 0.748-0.949), while there was a moderate agreement between FNAC and histopathology (κ= 0.620, 95%CI= 0.5192-0.638).